Nanoparticle from Medinilla speciosa with Various of Encapsulating Agent and Their Antioxidant Activities Using Ferric Reducing Assay - Vifta, Rissa Laila; Luhurningtyas, Fania Putri (Indonesian Society for Cancer Chemoprevention, 2020)
Antioxidants are agents that can reduce free radicals. Parijoto fruit (Medinilla speciosa) contains flavonoids that could act as an antioxidant. However, those flavonoids are water-soluble and show low bioavailability. Nanotechnology is a potential approach to improve the bioavailability of flavonoids from Parijoto fruit. This study was conducted to determine the antioxidant activity of parijoto nanoparticles with variations of the chitosan, alginate, and chitosan/alginate encapsulants. Secondary metabolites of parijoto fruit were using the maceration method. The synthesis of parijoto nanoparticles was conducted using the ionic gelation method with chitosan, alginate, and chitosan/alginate encapsulation. Parijoto nanoparticle size and distribution were characterized using Particle Size Analyzer (PSA). The formation of nanoparticles in colloids was determined as a percent. The antioxidant activity of nanoparticle was evaluated using Ferric Reducing Antioxidant Power (FRAP) method using a UV-Vis spectrophotometer. Chitosan encapsulation produced nanoparticles with a size of 269.3 nm, pdI 0.372 and transmittance 99.379%. Alginate encapsulation produced a particle size of 366.4 nm, pdI 0.589 and transmittance 99.690%. The combination of chitosan/alginate encapsulants produced a particle size of 187.00 nm, pdI 0.239 and transmittance 99.894%. Parijoto nanoparticles obtained from chitosan, alginate, and chitosan/alginate encapsulant showed strong antioxidant powers indicated by IC50 values 2.442±0.047 ppm, 3.175±0.169 ppm and 2.115±0.045 ppm, respectively. Altogether, our study shows that parijoto nanoparticles are potent as antioxidant agents.Keywords: Alginate, antioxidant, chitosan, FRAP, Medinilla speciosa, nanoparticle